Pengaruh kerjasama ekonomi Indonesia dengan China terhadap pertumbuhan ekonomi Indonesia - Muhammad alfikri; Mike Triani (Media Riset Ekonomi Pembangunan (MedREP), 2025)
This study aims to analyze the impact of Indonesia–China economic cooperation on Indonesia’s economic growth during the quarterly period of 2017–2024. The independent variables consist of Indonesia’s exports to China, imports from China, Foreign Direct Investment (FDI) from China, and the rupiah exchange rate against the US dollar, while the dependent variable is Indonesia’s economic growth. The research employs a quantitative approach using multiple linear regression (OLS) and classical assumption tests to ensure the validity of the model